Moldless PEGDA-Based Optoelectrofluidic Platform for Microparticle Selection. (3rd August 2011) - Yang, Shih-Mo; Yu, Tung-Ming; Liu, Ming-Huei; Hsu, Long; Liu, Cheng-Hsien
Abstract : This paper reports on an optoelectrofluidic platform which consists of the organic photoconductive material, titanium oxide phthalocyanine (TiOPc), and the photocrosslinkable polymer, poly (ethylene glycol) diacrylate (PEGDA). TiOPc simplifies the fabrication process of the optoelectronic chip due to requiring only a single spin-coating step. PEGDA is applied to embed the moldless PEGDA-based microchannel between the top ITO glass and the bottom TiOPc substrate. A real-time control interface via a touch panel screen is utilized to select the target 15 μ m polystyrene particles. When the microparticles flow to an illuminating light bar, which is oblique to the microfluidic flow path, the lateral driving force diverts the microparticles. Two light patterns, the switching oblique light bar and the optoelectronic ladder phenomenon, are designed to demonstrate the features. This work integrating the new material design, TiOPc and PEGDA, and the ability of mobile microparticle manipulation demonstrates the potential of optoelectronic approach.